Pronunciation-Focused Exercises in the 12th Grade English Language Textbook in Jordan - القاضي, كفاح ركان (Latakia University Journal - Arts and Humanities Sciences Series, 2021)
The present study aims at analyzing the pronunciation-focused exercises in the English language textbook for the twelfth grade in Jordan. The researcher analyzed the ( Student Book ) that is taught to the students in the 12th grade in public schools in Jordan. The student Book contains 5 Modules that include 10 units. The analysis revealed that not all units include pronunciation-focused exercises; and the ones that contain such exercises are: 2, 3, 4, 5, 6 and 8. The exercises briefly present: Using the International Phonetic Alphabets (IPA), Minimal Pairs, Word Stress and Sentence Stress. The analysis showed that the activities present few consonants and vowels among which sounds that are not found in the Arabic language, the students’ mother tongue. In addition, the review of these sounds do not form enough input that enables the learners to distinguish them. The activities that introduce minimal pairs, stress, and intonation tend to be convenient and suitable. Finally, the researcher presents some recommendations to improve teaching and designing pronunciation skills for EFL students.